CGIAR Research Program on Wheat - Plan of Work and Budget 2019 - CGIAR Research Program on Wheat (CGIAR Research Program on Wheat, 2019)
WHEAT is a CGIAR Research Program launched in 2012 and led by the International Maize and Wheat Improvement Center (CIMMYT). Joining advanced science with field-level research and extension in lower- and middle-income countries, WHEAT works to raise the productivity, production and affordable availability of wheat for 2.5 billion resource-poor consumers who depend on the crop as a staple food. R4D is carried out by a community of more than 200 public and private organizations worldwide; among them national governments, companies, international centers, regional and local agencies and farmers. WHEAT management includes experts from the Australian Centre for International Agricultural Research (ACIAR), the British Biotechnology and Biological Sciences Research Council (BBSRC), the International Center for Agricultural Research in the Dry Areas (ICARDA) and the Indian Council of Agricultural Research (ICAR). Funding for WHEAT comes from CGIAR System donors and others, including national governments, foundations, development banks and other public and private agencies. The Program thanks all donors and organizations who globally supported its work through their contributions to the CGIAR system